Sickness Absence and Local Cultures - Kristin Ekblad; Mattias Bokenblom (Örebro University School of Business, 2010)
Sickness absence has been found to vary substantially across geographical areas. There are large differences between different countries but also between different regions within a particular country. In the literature some of these observed differentials have been suggested to stem from differences in local norms with regard to the legitimacy of living off benefits. The aim of our study is to investigate the effect of geographical and presumed cultural context on sickness absence. In order to identify this effect we compare changes in sickness related absence for individuals who move from one Swedish region to another with those occurring when individuals move within Swedish regions. Our results indicate that the region of residence is important to the individual sickness related absence. Moreover, we cannot rule out the possibility that the observed patterns are caused by local cultures regarding sickness absence and the existence of a so called "cultural illness".
Keywords: J22; R23; Z13; 330; Sickness absence; social norms; domestic migration